A Non‐aqueous H3PO4 Electrolyte Enables Stable Cycling of Proton Electrodes. (23rd September 2020) - Xu, Yunkai; Wu, Xianyong; Jiang, Heng; Tang, Longteng; Koga, Kenneth Y.; Fang, Chong; Lu, Jun; Ji, Xiulei
Abstract: A non‐aqueous proton electrolyte is devised by dissolving H3 PO4 into acetonitrile. The electrolyte exhibits unique vibrational signatures from stimulated Raman spectroscopy. Such an electrolyte exhibits unique characteristics compared to aqueous acidic electrolytes: 1) higher (de)protonation potential for a lower desolvation energy of protons, 2) better cycling stability by dissolution suppression, and 3) higher Coulombic efficiency owing to the lack of oxygen evolution reaction. Two non‐aqueous proton full cells exhibit better cycling stability, higher Coulombic efficiency, and less self‐discharge compared to the aqueous counterpart. Abstract : The proton as a charge carrier offers a vast potential for battery systems with characteristics of high power and long longevity. A non‐aqueous proton electrolyte of anhydrous H3 PO4 solvated in acetonitrile for proton batteries is presented. It facilitates stable cycle performance of electrode materials that otherwise lose capacity rapidly in aqueous electrolytes.